The rewriting of historical spaces through the theatrical process of Negro Cosme em Movimento, by Cena Aberta Group (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
The artistic movements of retaking the urban space in the sixties and seventies were relatively documented and investigated in their creative and political contexts. At the same time, the expansion of research in arts into contexts that are still facing the process of obtain autonomy allows access to drama experiences in which there is an overlap between space and the resumption of its territorial history. This essay looks into the theater play Negro Cosme em Movimento, performed during the years 2013 to 2016, in the cities of Maranhão, by the theater Group Cena Aberta.  Using the approach mentioned above, it is possible to recognize in this theatrical experience the operationalization of notions in contemporary theater such as: “real theatre” and “site-specific theater”. The aim of this investigation is to document the remains of contemporary theatricality and its reverberations in territorial contexts where theoretical discussions in this area are missing.
Keywords: Contemporary theater; Theatrical Process; Historical Spaces; Site-Specific Theater; Cena Aberta Group